The “Second Lost Generation”: a Reading of Suburban Emptiness in Richard Yates’s Revolutionary Road - Castilho, Maria Teresa; Pacheco, Rita (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Paying close attention to the suburban landscape of the 1950s as conducive to a generalized malaise and anxiety caused by the strategy of conformity and domesticity in post-World War II America, this text offers a critical reading of the novel Revolutionary Road (1961), by Richard Yates (1926–1992). Taking as a starting point Yates’s understanding that the post-World War suburban generation was a “second lost generation”, as stated in his novel Young Hearts Crying, we will discuss the claustrophobia and the inescapable mundanity caused by the suburbs, from where the characters in Revolutionary Road dream to escape, seeming thus to follow the path of the bohemian Lost Generation of the 1920s. In his biography of Richard Yates, entitled A Tragic Honesty: The Life and Work of Richard Yates, Blake Bailey describes the author as an “unabashed worshipper” of F. Scott Fitzgerald, and The Great Gatsby as Yates’s “formal introduction to the craft” and “the definitive milestone of his apprenticeship”. Revolutionary Road is a novel that explores the contradictions in pursuing dreams and fantasies, where, as Steven Goldleaf states, “[we find a] persistent theme of characters striving toward some ideal of behaviour and always falling short of achieving that ideal.”